(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article highlights the relevance of using semi-finished dry batter based on oleogels for the development of an assortment of dessert products based on it, various flavor and aroma fillers and other additional ingredients that will form an assortment of desserts. The purpose of the work, the object and the subject of the research are determined. To obtain model systems, a foam-emulsion base obtained from semi-finished dry batter based on oleogels was used as the base of the dessert. During the technological tests, the rational content of food ingredients that can be used for the production of dessert products was substantiated. The content of food ingredients and raw materials that form the organoleptic indicators of finished products and ensure the formation of an assortment of dessert products with a foam-emulsion structure has been scientifically substantiated, and their influence on the foam-forming ability, stability and mechanical strength of foams has been determined. The expediency of introducing stabilizers in order to obtain foam emulsion systems with high mechanical strength is justified. It is shown that stabilizers must be administered in a hydrated state. It was established that as a structure former it is expedient to use quick-dissolving gelatin to regulate the consistency of foam emulsion products at a content of 1.0...2.0%, which provides high foaming capacity (710...750%), foam stability (99±1%) and mechanical strength (1440 ...1510 Pa). The use of semi-finished dry whipped cream with the use of oleogels in the composition of dessert products with a foam-emulsion structure is substantiated, and the ways of expanding its assortment are determined. The main physical and chemical parameters are determined. On the basis of experimental data, the technological parameters of the production of dessert products based on semi-finished dry whipped cream with the use of oleogels were determined.